The effects of exogenous application of melatonin on the degradation of polycyclic aromatic hydrocarbons in the rhizosphere of Festuca. (1st April 2021) - Rostami, Saeid; Azhdarpoor, Abooalfazl; Baghapour, Mohammad Ali; Dehghani, Mansooreh; Samaei, Mohammad Reza; Jaskulak, Marta; Jafarpour, Sima; Samare-Najaf, Mohammad
Abstract: The study aimed to assess the effects of melatonin, a plant growth regulator, on the degradation of phenanthrene (Phe) and pyrene (Py), in the rhizosphere of the Festuca grass. The experiments were divided into the following groups: 1) soil contaminated with Phe and Py, without the Festuca, 2) contaminated soil +  Festuca, 3–5), contaminated soil +  Festuca  + the application of melatonin in three separate doses: 10, 50, or 100 μM. After 90 days, the effects of melatonin supplementation on the degradation of polycyclic aromatic hydrocarbons (PAHs) were analyzed by evaluating the rate of PAHs degradation, the expression of genes encoding salicylaldehyde dehydrogenase (SDH) and glutathione peroxidase (GPX) enzymes in Pseudomonas putida, as well as by measuring the total activity of dehydrogenase and peroxidase enzymes. Our results have shown that in soil contaminated by 300 mg kg −1 PAHs, application of melatonin (10, 50, 100 μM), resulted in the following increase in the dehydrogenase and peroxidase activity in all three applied doses (19% and 5.7%), (45.3% and 34.3%), (40.9% and 14.3%), respectively in comparison to the control group. The experiment showed that soil supplementation with melatonin at 50 μM, resulted in the highest removal rate of PAHs. According to our results, melatonin demonstrated a potentially favorable role in enhancing plant biomass, as well as an increase in soil bacterial population, and the activity of antioxidative enzymes in P. putida, causing all tested parameters of the soil and the expression of desired genes to be advantageously altered for the degradation of the chosen PAHs. Graphical abstract: Image 1 Highlights: Melatonin increases the removal of PAHs from the soil. Melatonin protects Festuca against environmental pollutants and oxidative stress. The activity of peroxidase and dehydrogenase improves after melatonin application. The expression of genes encoding the enzymes SDH and GPX increases by melatonin.